The Future of Agile in Healthcare: Automating Claims Processing and Improving Patient Outcomes - Wazahat Ahmed Chowdhury (International Journal of Medical Science and Public Health Research, 2025)
The healthcare industry faces a transformative moment because Agile methods together with automation technology will transform Medicare and Medicaid claims processing and bring improvements to patient results. The existing healthcare processing systems face ongoing obstacles which include errors in outputs while taking too much time to process procedures as well as demanding HIPAA compliance rules. Through integration of Agile principles with AI and RPA and blockchain and IoT platforms the healthcare industry attains operation improvements along with cost reductions and better patient experiences in care delivery. Agile healthcare development moves toward automation in claims processing with its effects on patient results as a primary focus. This paper analyses newly emerging technologies plus implementation methods while studying difficulties and practical case studies by using best examples of practice. Healthcare organizations use Agile methods with automation to drive operational superiority and stronger healthcare results and better conformity to regulations.